PlaSA Colombia, Community of Practice in Food Systems - Rivas, Juan Sebastián; Muñoz, Luis Armando; Salas, Daniela (CGIAR System Organization, 2023)
On April 27, 2023, the launch of the PlaSA Colombia platform took place at the Los Andes University, Bogota Colombia, with the support of the CGIAR initiative on National Policies and Strategies (NPS), under the leadership of the Alliance of Bioversity and CIAT (International Center for Tropical Agriculture) in Colombia. This launch allowed a second meeting in which the allied entities of the platform were convened and had the opportunity to create the community of practice “PlaSA Colombia COMMUNITY OF PRACTICE IN FOOD SYSTEMS”, a community that brings together academy, research, and private sector with the intention to contribute, influence and actively impact on food systems in Colombia.